Pengaruh Literasi Keuangan dan Persepsi Manfaat Terhadap Minat Penggunaan E-Wallet Mahasiswa Prodi S1 Akuntansi Universitas Dian Nuswantoro - Chela Diva Aurellia; Ira Septriana; Ngurah Pandji Mertha Agung Durya; Imang Dapit Pamungkas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of financial literacy and perceived benefits on the interest in using e-wallets among students of the Bachelor of Accounting program at Dian Nuswantoro University. The development of financial technology has driven an increase in the use of e-wallets as a practical and efficient digital payment method, particularly among students. This study employs a quantitative approach using a survey method through an online questionnaire distributed to 85 respondents selected using purposive sampling techniques. The data were analyzed using IBM SPSS version 27. The results indicate that financial literacy has a negative and significant effect on the interest in using e-wallets, while perceived benefits have a positive and significant effect on the interest in using e-wallets. Among the two, perceived benefits proved to be the most dominant factor in driving interest in usage. These findings support the Technology Acceptance Model (TAM), which emphasizes that the perceived usefulness of technology is a primary determinant in the intention to adopt technology. This study suggests the need to enhance financial literacy and strengthen the perceived benefits of e-wallets among students to encourage more optimal use of financial technology.